Perancangan Data Warehouse CV.Al-Ghuroba' Sukoharjo - Darmasto, Rian Aditya; , Fatah Yasin Al Irsyadi, S.T.,M.T (2016)
CV.Al-Ghuroba' is a company engaged in the production and distribution of natural herbal products, located in ukoharjo regency, Central Java province. CV.Al-Ghuroba' have transaction data very much and accumulate over time, it would be very useful if the data is processed and will generate strategic information for the company. With data warehouse technology, the transaction data is classified according to the needs and then processed through the ETL (extraction, transformation, loading). The scheme is applied using a snowflake scheme produces four tables dimension, three tables sub-dimension, and the sales fact table that contains the measure as a information and primary key each dimension tables. The results of ETL process in the form of reports for strategic information by product category in a certain city at a certain time (year, quarter, and month). Data warehouse CV.Al-Ghuroba' can be accessed using a system that has been built with the java programming language dekstop based.